The Iconography of the Goddess Ninhursag - Steinkeller, Piotr ca. 20. Jh. (Journal of ancient Near Eastern religions, 2025)
This communication discusses the enigmatic representation of a Mesopotamian birth-goddess that appears on a group of Old Babylonian clay plaques. The goddess, who may be identified as Ninhursag/Ninmah, is shown offering bread to three infants. On the bottom, at either side of the goddess, a crouching, emaciated male is depicted. Scholars have formerly identified these two figures as either kūbu demons or human fetuses. It is argued here that, instead, these two individuals are to be explained as the victims of famine. Accordingly, it is concluded that these plaques depict the goddess as both a life-giving and nourishing motherly figure and a source of hunger and destruction. Textual data illustrating this dual nature of Ninhursag/Ninmah are cited in support of this interpretation.